Chiral Sulfones via Single-Electron Oxidation-Initiated Photoenzymatic Catalysis - Sakthivel, Pandaram; Shi, Qinglong; Ye, Juntao (Synlett, 2024)
We recently achieved an oxidation-initiated photoenzymatic enantioselective hydrosulfonylation of olefins through the utilization of a new Gluconobacter ene-reductase mutant (GluER-W100F-W342F). Our method simplifies the reaction system by eliminating the need for a cofactor regeneration mixture and, in contrast with previous photoenzymatic systems, does not depend on the formation of an electron donor–acceptor (EDA) complex between the substrates and enzyme cofactor. Moreover, the GluER variant exhibits good substrate compatibility and excellent enantioselectivity. Mechanistic investigations indicate that a tyrosine-mediated HAT process is involved and support the proposed oxidation-initiated mechanism. In this Synpacts article, we discuss the conceptual framework that led to the discovery of this reaction and reflect on the key aspects of its development.1 Introduction2 Conceptual Background2.1 Intramolecular Photoenzymatic Reactions via Single-Electron Reduction2.2 Intermolecular Photoenzymatic Reactions via Single-Electron Reduction3 The Development of the Process4 Conclusion
Keywords: photoenzymatic catalysis; hydrogen atom transfer; hydrosulfonylation; single-electron oxidation; directed evolution